[Translated article] Versatility of Tunneled Island Flaps for the Reconstruction of Facial Defects - M. Rogel-Vence; M. Carmona-Rodríguez; F. Moro-Bolado; L. González-Ruiz; M.P. Sánchez-Caminero; G. Romero-Aguilera (Elsevier, 2022)
Background and objective: Tunneled island flaps that transfer skin from a site adjacent to the wound are an effective way to reconstruct defects. These flaps provide good aesthetic and functional results and can be completed during a single surgical session, thus reducing complications. The procedure consists of taking an island of skin about the size of the surgical defect and moving it through a subcutaneous tunnel to cover the wound. We aimed to exemplify the use of these flaps in different regions of the face. Material and methods: Retrospective descriptive study of 12 cases in which tunneled island flaps were used after removal of malignant tumors in different facial regions. Results: The tumors, all of which were basal cell carcinomas, were removed by means of conventional surgery from 9 patients and Mohs micrographic surgery from 3 patients. Histology demonstrated tumor-free margins after excision in all cases. None of the tumors recurred during a mean follow-up period of 25 months. All complications were minor and transient. There were 3 cases of trapdoor effect and 2 each of postsurgical bleeding, transient superficial flap necrosis, and slight protrusion of the pedicle. The final cosmetic and functional outcome was satisfactory in all cases. Conclusions: Tunneled island flaps are particularly useful for repairing defects in the center of the face, where several anatomical structures converge. These flaps, which use donor skin that is similar to skin in the receptor site, can be used to close large defects in one-step procedures with only slight alteration of the facial architecture. Resumen: Introducción y objetivos: El colgajo en isla tunelizado (CIT) supone una opción eficaz para la reparación de grandes defectos faciales trasponiendo piel desde una unidad anatómica adyacente. La realización del colgajo aporta buenos resultados estéticos y funcionales en un único tiempo quirúrgico, evitando así complicaciones. El procedimiento consiste en labrar una isla de piel de dimensiones similares a las del defecto original, para luego desplazarla a través de un túnel subcutáneo a la región receptora. Nuestro objetivo es ejemplificar su uso en diferentes regiones de la cara. Material y métodos: Estudio descriptivo retrospectivo de 12 casos con reconstrucción mediante CIT tras la extirpación de tumores malignos en distintas áreas faciales. Resultados: Presentamos una serie de 12 casos intervenidos de carcinoma basocelular, 9 mediante cirugía convencional y 3 mediante cirugía de Mohs. El estudio histológico mostró bordes quirúrgicos libres en todas las piezas de resección. El tiempo medio de seguimiento fue de 25 meses sin detectarse recidivas tumorales. Las complicaciones fueron menores y temporales: efecto trampilla en 3 pacientes, hemorragia posquirúrgica en 2, necrosis superficial transitoria del colgajo en 2 y protrusión leve del pedículo en 2 casos. El resultado final cosmético y funcional fue satisfactorio en todos los casos. Conclusiones: Los CIT son especialmente útiles en defectos centrofaciales donde convergen distintas unidades anatómicas. Permiten la reconstrucción en un único tiempo quirúrgico de grandes defectos faciales, aportando piel de características similares a las de la zona receptora y alterando mínimamente la arquitectura facial.